Linear Predictive Detection for Power Line Communications Impaired by Colored Noise. (26th June 2007) - Pighi Pighi, Riccardo Riccardo; Raheli Raheli, Riccardo Riccardo
Abstract : Robust detection algorithms capable of mitigating the effects of colored noise are of primary interest in communication systems operating on power line channels. In this paper, we present a sequence detection scheme based on linear prediction to be applied in single-carrier power line communications impaired by colored noise. The presence of colored noise and the need for statistical sufficiency requires the design of an optimal front-end stage, whereas the need for a low-complexity solution suggests a more practical suboptimal front-end. The performance of receivers employing both optimal and suboptimal front-ends has been assessed by means of minimum mean square prediction error (MMSPE) analysis and bit-error rate (BER) simulations. We show that the proposed optimal solution improves the BER performance with respect to conventional systems and makes the receiver more robust against colored noise. As case studies, we investigate the performance of the proposed receivers in a low-voltage (LV) power line channel limited by colored background noise and in a high-voltage (HV) power line channel limited by corona noise.